One-step synthesis of magnetic 1, 6-hexanediamine-functionalized reduced graphene oxide–zinc ferrite for fast adsorption of Cr(vi)1. Issue 40 (7th May 2015) - Li, Haizhen; Zhang, Li; Sun, Zebin; Liu, Yan; Yang, Bo; Yan, Shiqiang
<x xml:space="preserve">Abstract</x> A one-step solvothermal method was developed to prepare nearly cubic ZnFe2O4 nanoparticles loaded on 1, 6-hexanediamine-functionalized reduced graphene oxide (HDA–RGO–ZnFe2O4) for fast removal of Cr(vi).